Future mathematics and informatics to their teacher’s network technologies science training (Texas Journal of Engineering and Technology, 2022)
This in the article "Network technologies" science in learning in students modern information and communication technologies own professional in the activity conscious and critical point of view mean apply ability formation to the problem dedicated.